Body dissatisfaction and concern, body checking and avoidance behavior in people with eating disorders - Campana, Angela Nogueira Neves Betanho (2012)
The aim of this study was to investigate aspects of body image in a sample of people with anorexia nervosa, bulimia nervosa and eating disorder not otherwise specified. The sample was composed of 14 volunteers, cared for by the Eating Disorders Outpatients Clinic, from Universidade Estadual de Campinas. The Software for Perceptual Assessment (SPA) assesses body dissatisfaction. The variables body concern, checking behavior and avoidance behavior were assessed by the Body Shape Questionnaire, Body Checking Questionnaire and Body Image Avoidance Questionnaire, in this order. The descriptive analysis and correlations indicate high levels of dissatisfaction, checking behavior, avoidance behavior, and concern over the body, with significant associations. These findings showed the importance of the investigated parameters for the dynamic of the disease. Knowing these body image components could expand the possibilities of understanding how these patients organize their body representations and carefully plan interventions during the course of the treatment.